Factors Affecting Stock Return in Indonesian - Irwan, Irwan; Etty Murwaningsarih; Sekar Mayangsari (Dinasti International Journal of Economics, Finance & Accounting, 2023)
The motivation behind this research is to determine the impact of earnings management, transfer pricing (TPRC), corporate social responsibility (CSR) on stock returns (RS) moderated by foreign ownership. The research used is secondary from the Indonesia Stock Exchange for the 2016-2021 period. Selection of the study sample. The method used was purposive sampling with a model. The number of samples used was 205 in five years (2015-2019). Data processing was performed using path analysis techniques at a significance level of 0.05. The results of the study explain that the Stubben model of earnings management (EMS), transfer pricing (TPRC) and CSR have a significant effect on stock returns (RST). Foreign ownership (FOR) managed to moderate the effect of transfer pricing (TPRC), CSR on stock returns (RST). However, foreign ownership (FOR) failed to moderate earnings management (EMS) on stock returns (RS).